HUBUNGAN DUKUNGAN KELUARGA DAN SOSIAL EKONOMI DENGAN PEMILIHAN TEMPAT PERSALINAN DI PUSKESMAS TEBING TINGGI - Ruri Maiseptya Sari; Sanisahhuri Sanisahhuri; Martini Martini (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2020)
Background: One of the factors of the high MMR in Indonesia is due to the relatively low coverage of help by health workers. Puprose: The purpose of this study was to determine the relationship of family and socioeconomic support with the choice of delivery place in Puskesmas Tebing Tinggi. Methods: This study is analytic survey with cross sectional design. The research population in this study was trimester III pregnant women in Puskesmas Tebing Tinggi in July 2019, amounting to 52 people. The sample in this study was third trimester pregnant women who are in Tebing Tinggi Health Center taken in total sampling. Data collection is done using primary data. Results: The results of the study of 52 pregnant women respondents who chose non-health service facilities were 31 respondents and those who chose health service facilities were 21 respondents. From 52 family respondents who support as many as 30 respondents and do not support as many as 22 respondents, from 52 respondents with socioeconomic <UMR as many as 35 respondents and ? UMR as many as 17 respondents. Chi-square test results obtained value ?2 = 4.278 with p value = 0.05 meaning that there is a relationship of family support with the choice of delivery place in Tebing Tinggi Health Center with a moderate category. Chi-square test results (Pearson chi-square) obtained value ?2 = 8.27 with p value = 0.05 means that there is family support by choosing the place of delivery at Tebing Tinggi Health Center with a moderate category. Conclusion: It was concluded that there was a significant relationship between family support and socio-economics with the choice of delivery place in the Tebing Tinggi Health Center with a moderate category.Keywords: Family Support; Economic Sociology; Selection of Childbirth